2020
DOI: 10.1016/j.placenta.2020.03.011
|View full text |Cite
|
Sign up to set email alerts
|

The placental programming hypothesis: Placental endocrine insufficiency and the co-occurrence of low birth weight and maternal mood disorders

Abstract: Polypeptide hormones and steroid hormones, either expressed by the placenta or dependant on the placenta for their synthesis, are key to driving adaptations in the mother during pregnancy that support growth in utero. These adaptations include changes in maternal behaviour that take place in pregnancy and after the birth to ensure that offspring receive appropriate care and nutrition. Placentally-derived hormones implicated in the programming of maternal caregiving in rodents include prolactin-related hormones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 115 publications
0
14
0
Order By: Relevance
“…However, we acknowledge that clinical and mechanistic research examining fetal sex-differential levels of these hormones and other biological effectors in relation to PPD remains limited. Other research has shown sex-differential expression of imprinted genes in the placenta that in turn have been linked to maternal mood disorders [62]. For example, PEG3 is an imprinted gene that plays important roles in controlling fetal growth and nurturing behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…However, we acknowledge that clinical and mechanistic research examining fetal sex-differential levels of these hormones and other biological effectors in relation to PPD remains limited. Other research has shown sex-differential expression of imprinted genes in the placenta that in turn have been linked to maternal mood disorders [62]. For example, PEG3 is an imprinted gene that plays important roles in controlling fetal growth and nurturing behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased placental expression of PEG3 has also been linked to perinatal depression in mothers [ 91 ]. Although again this is tentative, correlative evidence for a role in humans, the link between imprinted genes, placental function and maternal mental health is an exciting area for future study [ 92 ].…”
Section: Indirect Action Of Imprinted Genes On Brain and Behaviourmentioning
confidence: 99%
“…Normal growth and survival of the fetus depends on the adequate placentation. Besides providing sufficient amounts of nutrients and oxygen, the placenta establishes a privileged immune environment for fetal growth by orchestrating maternal adaptations to pregnancy and acting as a selective and protective barrier to prevent feto-maternal diseases (Creeth and John, 2020). Poor placentation and placental failure compromises fetal development leading to potential chronic diseases in adult (Sharma et al, 2016;Perez-Garcia et al, 2018;Woods et al, 2018).…”
Section: Introductionmentioning
confidence: 99%